Analysis of the composition, characteristics, and antifungal properties of cutin in goji berry fruits at different developmental stages - Zhou, Yueli; Chen, Dayuan; Wang, Cong; Zhang, Huaiyu; Zhao, Lunaike; Wang, Junjie; Peng, Qiding (Frontiers in Plant Science, 2025)
Cutin is the main component of the fruit cuticle framework and plays a role in resisting biological stress. However, little is known about the cutin composition and antifungal properties of goji berry (Lycium barbarum L.). In the current study, paraffin sections and gas chromatography/mass spectrometry (GC/MS) techniques were used to identify differences in cuticle structure and chemical composition of Ningqi-1 and Ningqi-5 goji berries at different developmental stages. Meanwhile, cutin extracts from goji berries at four developmental stages were evaluated for their effects on spore germination, germ tube elongation, and mycelial growth of A. alternata. Twenty-six cutin compounds were identified in Ningqi-1 and Ningqi-5. Fatty acids, alkanes, aromatic acids, and small molecule acids were the main components of goji berry cutin, which are related to the formation of cutin structures. Spore germination and germ tube elongation in A. alternata were significantly inhibited by treatment with cutin extracts from goji berries at different developmental stages. Moreover, the cutin monomer content in goji berries may be closely related to antifungal properties. This study provides a research basis for further investigation of the accumulation mechanism of natural antifungal substances during the growth and development of goji berries.